Role of echocardiographic scoring systems in predicting successful biventricular versus univentricular palliation in neonates with critical aortic stenosis. (3rd November 2020) - Sachdeva, Shagun; Kuhn, Evelyn; Frommelt, Peter C.; Handler, Stephanie
Abstract: Background: There are several published echo-derived scores to help predict successful biventricular versus univentricular palliation in neonates with critical aortic stenosis. This study aims to determine whether any published scoring system accurately predicted outcomes in these neonates. Methods: Single centre, retrospective cohort study including neonates who underwent aortic valve intervention (surgical valvotomy or balloon valvuloplasty) with the intention of biventricular circulation. Primary outcome was survival with biventricular circulation at hospital discharge. Data from their initial neonatal echocardiogram were used to compute the following scores – Rhodes, CHSS 1, Discriminant, CHSS 2, and 2 V. Results: Between 01/1999 and 12/2017, 68 neonates underwent aortic valve intervention at a median age of 4 days (range 1–29 days); 35 surgical valvotomy and 33 balloon valvuloplasty. Survival with biventricular circulation was maintained in 60/68 patients at hospital discharge. Of the remaining eight patients, three were converted to univentricular palliation, four died, and one underwent heart transplant prior to discharge. None of the binary score predictions of biventricular versus univentricular (using that score's proposed cut-offs) were significantly associated with the observed outcome in this cohort. A high percentage of those predicted to need univentricular palliation had successful biventricular repair: 89.4% by Rhodes, 79.3% by CHSS 1, 85.2% by Discriminant, and 66.7% by CHSS 2 score. The 2 V best predicted outcome and agreed with the local approach in most cases. Conclusion: This study highlights the limitations of and need for alternative scoring systems/cut-offs for consistently accurate echocardiographic prediction of early outcome in neonates with critical aortic stenosis.